2023
DOI: 10.1186/s12889-023-16906-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between magnesium, copper, and potassium intakes with risk of rheumatoid arthritis: a cross-sectional study from National Health and Nutrition Examination Survey (NHANES)

Jianguo Fang,
Tingwei Cao,
Cai Liu
et al.

Abstract: Background The relationship between Mg (magnesium), Cu (copper), and K (potassium) intakes and the risk of rheumatoid arthritis (RA) remains limited. The aim of present study was to examine the associations between Mg, Cu and K intakes with RA. Methods Using data from the National Health and Nutrition Examination Survey (NHANES) 2003–2018, we examined the association between Mg, Cu and K intakes and the risk of RA among US adults. After adjustment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…22 In research utilizing data from NHANES spanning 2003 to 2018, increased magnesium consumption might be inversely related to RA risk in the adult population of the United States. 14 This study demonstrated that the composite measurement of dietary total antioxidant consumption from food (CDAI) was associated with an increased risk of RA. Earlier investigations have also documented links between CDAI and diverse diseases.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…22 In research utilizing data from NHANES spanning 2003 to 2018, increased magnesium consumption might be inversely related to RA risk in the adult population of the United States. 14 This study demonstrated that the composite measurement of dietary total antioxidant consumption from food (CDAI) was associated with an increased risk of RA. Earlier investigations have also documented links between CDAI and diverse diseases.…”
Section: Discussionmentioning
confidence: 92%
“…13 A previous study indicated that a higher magnesium intake may be inversely associated with the risk of RA among US adults. 14 Another study found that vitamin E supplementation can improve symptoms of RA and improve patients' quality of life. 15 However, dietary nutrients tend to be simultaneously present, and it is more clinically relevant to study the intake of multiple dietary antioxidants than to study a single antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, our research found intakes of phosphorus, protein, potassium, and vitamin B1 were also negatively associated with accelerated aging. While there was no direct evidence to validate the association between these nutrients and accelerated aging, studies have emphasized the potential role of these nutrients in the prevention of related diseases such as sarcopenia, rheumatoid arthritis, cancer, and others [ 21 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that sex differences did not have a significant impact on the causal relationships between dietary supplementary intake and the risk of ARDs. For example, Fang et al ( 92 ) examined the relationship between the intake of essential micronutrients, including Mg (magnesium), Cu (copper), and K (potassium), and Fe (iron), and the risk of rheumatoid arthritis (RA) among US adults. After adjustment for age, sex, race, BMI, educational level, smoking history, alcohol consumption, family poverty income ratio (PIR), diabetes status and total daily energy intake, logistic regression models and smooth curve fitting were applied to examine the associations of Mg, Cu and K intake with RA.…”
Section: Limitations and Strengthsmentioning
confidence: 99%